Respuesta :

Answer:

f =  3x^2+ 1  / x

Step-by-step explanation:

Let's solve for f.

fx=3x2+1

Step 1: Divide both sides by x.

fx  / x  =  3x^2+1  / x

f=  3x2+1  / x

Answer:

see explanation

Step-by-step explanation:

Given

f(x) = 3x² + 1

To obtain f(- 1) substitute x = - 1 into f(x) , that is

(8)

f(- 1) = 3(- 1)² + 1 = 3(1) + 1 = 3 + 1 = 4

(9)

Similarly

f(0) = 3(0)² + 1 = 3(0) + 1 = 0 + 1 = 1

(10)

Given

f(x) = 3x² + 1 and f(x) = 49, then equate right sides

3x² + 1 = 49 ( subtract 1 from both sides )

3x² = 48 ( divide both sides by 3 )

x² = 16 ( take the square root of both sides )

x = ± [tex]\sqrt{16}[/tex] = ± 4

That is x = - 4 or x = 4

ACCESS MORE